Pengaruh Kualitas Layanan Personal Trainer Dan Customer Experience Terhadap Loyalitas Pelanggan Gym - Muhamad putra jovabzah; Rini Anggriani; Lady Faerrosa; L. Jatmiko Jati; M. Chothibul Umam Assa’ady (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of personal trainer service quality and customer experience on gym customer loyalty in Mataram City. The study was conducted due to the phenomenon in Mataram City of intense business competition in the gym industry, which requires business owners to pay attention to providing quality personal trainer services, adequate facilities, and the ability to understand the conditions and situations of each different customer in order to increase gym customer loyalty. The method used in this study is quantitative with a causal approach. Data collection was conducted by distributing questionnaires to 160 respondents with a population of gym members and customers using personal trainer services. The criteria for customers are gym members for a minimum of 2 months, use personal trainer services, and are aged 17 years or older. Data processing tools used are SPSS 22. The data analysis techniques used were validity and reliability tests, classical assumptions, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results showed that the quality of personal trainer services had a positive and significant effect on customer loyalty. However, the customer experience variable had a positive but insignificant effect on customer loyalty. Simultaneously, both variables had a significant effect on customer loyalty. This indicates that improving the quality of personal trainer services can increase customer loyalty, while customer experience does not necessarily have a direct, significant impact.